VALIDITAS DAN RELIABILITAS ANGKET PENYESUAIAN DIRI PESERTA DIDIK SMA - Rizqi Zamilah Tussaadah; Heris Hendriana; Wiwin Yuliani (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
Self-adjustment is an individual's effort to achieve harmony with himself and his environment, so that feelings of hostility, envy, jealousy, prejudice, depression, anger and negative emotions as inappropriate and inefficient personal responses can be eroded out. From this understanding, self-adjustment is a natural and dynamic process that aims to change individual behavior so that there is a relationship that is more appropriate to the conditions of the environment. Seeing how important self-adjustment is for individuals even for students in new environments, a measuring tool is needed in the form of an self- adjustment questionnaire. This study uses research and development (R&D) development research to develop and validate educational products in the form of an self-adjustment questionnaire. The self-adjustment questionnaire required validity and reliability tests. The subjects of this study were students of SMA Negeri 1 Cipongkor. The results of the validity test of the self-adjustment questionnaire stated that 13 statements were valid and their reliability was 0.718 which was categorized as high from the 30 statements that the researcher made from 28 respondents.Keywords:  Self-Adjustment, Validity, Reliability